CYBERCRIME @ CITY HALL. - Cliff, Gerald (Public Management (00333611), 2015)
The article reports that there is an increase in identity theft and cybercrime in the U.S. Topics discussed include more exposure to personally identifiable information (Pll) due to rise in use of credit cards and digital currencies, the hacker group Anonymous, the Ponemon Institute's survey which focuses on cost of data breach and an analysis by the National White Collar Crime Center (NW3C) on ways PII data is compromised such as theft of electronic devices.